Toxocariasis: Seroprevalence in abandoned-institutionalized children and infants - Archelli, Susana Mónica (2014)
Toxocariasis is an infection that has worldwide distribution. Toxocara canis is the most relevant agent due to its frequent occurrence in humans. Soil contamination with embryonated eggs is the primary source of T. canis. This study aimed to determine the seroprevalence of toxocariasis in 10-month to 3 year-old abandoned infants, considered to be at high risk because of their orphanhood status and early age. Blood samples were collected from 120 children institutionalized in an orphanage in the city of La Plata. In this study, we observed 38.33% of seropositive cases for T. canis by ELISA and 45% by Western blot techniques; significant differences among groups A (<1 year), B (1-2 years) and C (>2 years) were also found. In research group A, children presented a seropositivity rate of 23.91%, in group B of 42.85% and in group C of 56%, which indicates an increase in frequency as age advances, probably because of greater chances of contact with infective forms of the parasite since canines and soil are frequently infected with T. canis eggs. Abandoned children come from poor households, under highly unsanitary conditions resulting from inadequate or lack of water supply and sewer networks, and frequent promiscuity with canines, which promotes the occurrence of parasitic diseases. These children are highly vulnerable due to their orphanhood status and age.